Dr. Rodolfo Herrera Jiménez, maestro de ingenieros: Una breve semblanza - Hidalgo Leiva, Diego A. (Universidad de Costa Rica, 2021)
On November 17, 2018, PhD Rodolfo Herrera Jiménez passed away. He will be remembered for his quality as a person, his vision, and his contributions both to the university and to the practice of structural and seismic engineering in Costa Rica. On July 10, 2019, the Permanent Commission of the Seismic Code of Costa Rica made a posthumous tribute to PhD Herrera, where members and former members of the Costa Rican Seismic Code, colleagues from the University of Costa Rica, his wife and sons participated. The editorial committee of this Journal has considered important to document part of the interventions carried out that day in combination with remembrances of people close to PhD. Herrera.